The role of sports Activities in achieving development from the point view of the staff in Physical education departments in Syrian Arab Republics - محمود حلا; وائل مارون معوض; سراج سمعان ديوب (Latakia University Journal -Medical Sciences Series, 2023)
The aim of the research is to identify the role of sports Activities in achieving development from the point view of the staff in Physical education departments in Syrian Arab Republics, it aims also to determine how the sports activities are activated in the sports related institutions. The descriptive methodology is used on the sample that includes (252) of teachers and supervisors of the sports field in the physical education departments. The study concludes that the sports Activities contributes to the development in general especially in the health and psychological developments. The sports Activities are affected by the administrative, personal and social aspects.